Perbandingan Administrasi Peradilan Dalam Keadaan Darurat (Judicial Emergency) Akibat Pandemi Covid-19 Di Amerika Serikat Dan Di Indonesia - Ibnu Sina Chandranegara (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The determination of a state of emergency clearly affects not only the executive and legislative branches of power but also the judicial power. The establishment of a state of emergency for the Covid-19 Pandemic in various countries has a direct or indirect effect on judicial powers in carrying out their duties and functions. This article is intended to compare the application of judicial emergency in the United States and how it reflects on judicial power in Indonesia. This study uses the comparative constitutional law method, which is to compare the material of constitutional law and practice in other countries to take the best materials and practices and provide suggestions that should be avoided in positive constitutional law. This article concludes that there is a need for strict legal material in the law of judicial powers and the procedural law in Indonesia so that it does not delegate too much technical authority in dealing with emergencies in the judiciary.